Human Resource Management Analysis in Improving Government Apparatus Performance in Simboro District, Mamuju Regency - A. Taufan, Sri Ulandari (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to analyze the role of human resource management in improving the performance of government apparatus at the Simboro Sub-district Office, Kabupaten Mamuju, Province of Sulawesi Barat. The research employed a quantitative method with a descriptive–associative approach to examine the relationship between human resource management and employee performance. The population consisted of 28 government employees working at the Simboro Sub-district Office. Using a saturated sampling technique, all employees were involved as research respondents. Data were collected through questionnaires, observation, and documentation. The data analysis techniques used included descriptive statistics, Pearson correlation analysis, and simple linear regression. The descriptive analysis shows that the implementation of human resource management is in the good category with an average score of 3.85 out of 5 (77.0%), while the performance of government apparatus is also categorized as good with an average score of 3.90 (78.0%). The results of the correlation analysis indicate that human resource management has a strong relationship with employee performance (r = 0.62). Furthermore, the regression analysis shows that human resource management has a positive and significant effect on the performance of government apparatus with a significance value of 0.003 < 0.05. The coefficient of determination (R²) value is 0.38, which means that 38% of the variation in employee performance can be explained by human resource management, while the remaining 62% is influenced by other factors outside the model. Based on the findings, it can be concluded that effective human resource management plays an important role in improving the performance of government apparatus at the Simboro Sub-district Office.